Pengaruh Posisi Elevasi Head Of Bed 300 Dibandingkan dengan Elevasi Head Of Bed 600 terhadap Peningkatan PaO2 dan Rasio PaO2/FiO2 pada Pasien dengan Ventilasi Mekanik di ICU RSUP Dr. Sardjito - Anindita, Triatma; Wisudarti, Calcarina Fitriani Retno; Rahardjo, Sri (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2022)
Background: Mechanical ventilation is the frequent reason of admitting patients to the Intensive Care Unit(ICU). Mechanical ventilation was used in resuscitating critical patient with lung disorder where the lung fails to oxygenite arterial blood. Patients with mechanical ventilation are more prone to immobilization because of the decrease of consciousness. Some researches had showed that the position change of patients with several conditions including mechanical ventilation increased the lung function thus resulting better blood oxygenation.Objectives: To compare the benefits of positioning patients with 600 HOB elevation to 300 HOB elevation by evaluating the PaO2 and PaO2/FiO2 ratio.Methods: This research was done with clinical trial using One Group Pretest Posttest. Patients was positioned first in the standard position (supine), elevation position Head of Bed (HOB) 300 and HOB 600. Then we measured the hemodynamic parameters, blood pressure, heart rate, respiratory parameters, peripheral O2 saturation and Blood Gas Analysis.Results: We obtained 21 subjects in this research 10 males and 11 females. We found significant increaseof PaO2 with elevation HOB of 600 compared to 300 (192.2 vs 160.7, p<0,05). The PaO2/FiO2 ratio showedsignificant increase in the HOB 600 (382.3 vs 322.2, p<0,05). The hemodynamic and respiratory parameters, we found that mean MAP, tidal volume, PIP and compliance in position of HOB elevation 600 were highercompared to the HOB elevation of 300 while the heart rate, resistance and PH were lower. But those differences were not statistically significant with p>0.05.Conclusion: The elevation head of bed 600 increase the PaO2 and PaO2/FiO2 ratio compared to the elevation head of bed 300 in patients with mechanical ventilation in ICU of RSUP Dr. Sardjito.